Injunctions in Patent Law Trans-Atlantic Dialogues on Flexibility and Tailoring - Contreras, Jorge L.; Husovec, Martin (Social Sciences, 2022)
Patents incentivize the creation and dissemination of new technical solutions and help to disclose their working to the public in exchange for limited exclusivity. Injunctions are vital tools for patent enforcement. This book explains how the drafting, tailoring and enforcement of injunctions in patent law works in several leading jurisdictions.